PENGARUH INTENSITAS PERSAINGAN DAN EFISIENSI PENAWARAN TERHADAP HASIL TENDER PROYEK JALAN DI LPSE KOTA BANJARMASIN (2016-2023) - Muhammad Hazairin; Mulyadi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2026)
The effectiveness of road infrastructure development depends heavily on procurement quality through electronic tendering mechanisms. Within the Electronic Procurement Service (LPSE) system, competition intensity and bidding efficiency are theoretically the primary determinants of tender outcome quality. However, no empirical study has specifically examined both factors in regional construction markets with unique geographical characteristics such as Banjarmasin City. This study aims to analyze the effect of competition intensity and bidding efficiency on road project tender outcomes in the Banjarmasin City LPSE for the period 2016–2023, both partially and simultaneously. A sample of 30 work packages was selected through purposive sampling from the Banjarmasin City LPSE portal. Analysis was conducted using multiple linear regression with a robust standard errors approach. The results indicate that competition intensity has a positive and significant effect (α = 10%), while bidding efficiency has a negative and significant effect (α = 5%) on tender outcomes. Simultaneously, both variables significantly influence tender outcomes with a coefficient of determination of 19.66%. These findings suggest that tender outcomes are not solely determined by the number of participants and price rationality, highlighting the need for a more comprehensive procurement approach in evaluating tender competition quality at the regional level.